A Case of Distal Epithelioid Sarcoma of the Thumb Expressing Podoplanin, TLE1 and Ca 125 - George Karagkounis; Theodore Argyrakos; G. Charkiolakis; O. Castana; D. Rontogianni (Case Reports in Pathology)
Distal epithelioid sarcoma is a rare and slowly growing tumor that usually develops in the upper extremities of young adults. Neoplastic cells have both spindle and epithelioid appearance and are characterized by the loss of the nuclear protein SMARCB1/INI1. We present the case of a distal epithelioid sarcoma arising in the thumb of a 14-year-old girl, which immunohistochemically was characterized by the loss of SMARCB1/INI1 protein as well as the expression of podoplanin (D2-40), TLE1, Glut1, and Ca 125; plus, we highlight the differential diagnosis of epithelioid sarcoma from its histological mimics.